Auction Of Execution Confiscated And National Confiscated - Cucuk Hariyadi; Timbul Mangaratua Simbolon; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The applicants auction sellers often in practice face prosecution or a lawsuit from a third party that the goods to be auctioned are their own and not the property of those who had been cut with a criminal offense, as it sometimes is the case / light after the auction conducted and considered have been completed. In addition to the auction buyer after he mastered the goods purchased from the auction process also sometimes face prosecution or a lawsuit from a third party that the goods he bought from the auction is actually owned by third parties. The purpose of this study is to analyze the legal protection given to the rightful owner of the auction the buyer of goods or execution of plunder and spoils the country carried out by KPKNL Yogyakarta. This type of research is empirical. Source data using primary and secondary data. The data were analyzed descriptively qualitative. The results showed that the form of legal protection to each of the parties related to the auction execution of plunder and booty state 1) Acting as seller / applicant auction execution is the police or the prosecutor.; 2) To the owner of the goods / owner beginning of good will get legal protection to prevent the auction execution if the auction is not conducted through the path objections / rebuttals, however, if the auction had been implemented, the original owner can file a lawsuit with the District Court, if based on the decisions of the Court the country was the original owner declared right then he can ask them to buyers KPKNL that the goods be returned; 3) To the auction buyers who have a good-faith execution of legal protection in the form of refund of the purchase that have been paid without any deduction. but if the auction had been implemented, the original owner can file a lawsuit with the District Court, if based on the District Court declared the original owner right then he can ask to the buyer that the goods be returned KPKNL.Keywords: Legal Protection; The Auction Execution; KPKNL Yogyakarta.